Doing research in the real world - Gray, David E. (Sage, 2018)
This helpful book takes a pragmatic, real-world approach to research methods that gives readers the tools and confidence to carry out their own research in and out of the classroom. Expertly weaving quantitative, qualitative, and mixed methods together, it encourages readers to be open-minded in choosing the most appropriate methods for their projects. Featuring a full set of updated and integrated digital resources, as well as three new chapters on visual methods, qualitative data analysis with NVivo, and digital research, the new Fourth Edition remains on the forefront of practical, applied research and guides readers through every step of the research process from start to finish. Brimming with checklists, interdisciplinary examples, and tips about navigating the realities of planning a project, collecting and analyzing data, and sharing research findings, Doing Research in the Real World is still the companion for any student undertaking a research project. --